2021
DOI: 10.1002/saj2.20205
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse reflectance infrared spectroscopy estimates for soil properties using multiple partitions: Effects of the range of contents, sample size, and algorithms

Abstract: The RMSE of validation (RMSE V ) and ratio of the interquartile range to RMSE V (RPIQ V ) are key quality parameters in diffuse reflectance infrared (IR) spectroscopy studies, but the effects of different factors on these parameters are often not sufficiently considered. Our objectives were to reveal the effects of range of contents, sample size, data pretreatment, wavenumber region selection, and algorithms on the evaluation of IR spectra in the wavenumber range from 1,000 to 7,000 cm −1 (mid-and long-wave ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…According to the authors, the OPS-PLSR improved the prediction accuracy of SOC as compared to the full spectrum approach but only slightly (Full-spectrum model for Alfisols: R 2 = .56, RPD = 1.53 and RMSE = 0.08%; OPS-PLSR for Alfisols: 0.57, 1.54, and 0.08%). Ludwig et al (2021) investigated the effects of SOC% range, sample size, and wavenumber region selection on the RMSE and RPIQ. They used an automatic method to select optimal models from more than 17,800 combinations of nine spectral regions between 7,000 and 1,030 cm −1 (MIR and long-range NIR) and spectral preprocessing treatments.…”
Section: Wavelength Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…According to the authors, the OPS-PLSR improved the prediction accuracy of SOC as compared to the full spectrum approach but only slightly (Full-spectrum model for Alfisols: R 2 = .56, RPD = 1.53 and RMSE = 0.08%; OPS-PLSR for Alfisols: 0.57, 1.54, and 0.08%). Ludwig et al (2021) investigated the effects of SOC% range, sample size, and wavenumber region selection on the RMSE and RPIQ. They used an automatic method to select optimal models from more than 17,800 combinations of nine spectral regions between 7,000 and 1,030 cm −1 (MIR and long-range NIR) and spectral preprocessing treatments.…”
Section: Wavelength Selectionmentioning
confidence: 99%
“…Lower RMSEs were associated with more homogeneous calibration models and higher RMSEs with more heterogeneous models; however, as Clingensmith et al (2019) found, more heterogeneous models also had a wider IQR resulting in higher RPIQs. The authors cautioned that RPIQ and RMSE values should not be interpreted independently in infrared studies, but rather in the context of their associated IQR values (Ludwig et al, 2021).…”
Section: Wavelength Selectionmentioning
confidence: 99%
See 3 more Smart Citations